Ocular Mucous Membrane Pemphigoid Demonstrates a Distinct Autoantibody Profile from Those of Other Autoimmune Blistering Diseases: A Preliminary Study - Yingzi Liu; Lei Bao; Dharm Sodha; Jing Li; Adrian Mansini; Ali R. Djalilian; Xiaoguang Li; Hua Qian; Norito Ishii; Takashi Hashimoto; Kyle T. Amber (Antibodies)
Background: Ocular predominant mucous membrane pemphigoid (oMMP) is a severe subtype of autoimmune blistering disease (AIBD), which can result in scarring and vision loss. The diagnosis of oMMP is challenging as patients often have undetectable levels of circulating autoantibodies by conventional assays. Likewise, the principal autoantigen in oMMP has been an area of debate. Methods: In this preliminary experiment, we performed Phage Immunoprecipitation Sequencing (PhIP-seq) on sera from patients with oMMP, as well as non-ocular MMP, bullous pemphigoid, and mucocutaneous-type pemphigus vulgaris. Results: We identified several autoantigens unique to oMMP relative to other AIBDs. We then cross-referenced these antigens against previously published single-nuclei datasets, as well as the International Mouse Phenotyping Consortium Database. Several protein hits identified in our study demonstrated enriched expression on the anterior surface epithelia, including TNKS1BP1, SEC16B, FNBP4, CASZ1, GOLGB1, DOT1L, PRDM 15, LARP4B, and RPL6. Likewise, a previous study of mouse knockout models of murine analogs CASZ1, HIP1, and ELOA2 reported that these mice showed abnormalities in terms of the ocular surface and development in the eyes. Notably, PhIP-seq failed to identify the canonical markers of AIBDs such as BP180, BP230, desmogleins 1 and 3, or integrin β4, indicating that the patient autoantibodies react with conformational epitopes rather than linear epitopes. Conclusions: oMMP patients demonstrate a unique autoantibody repertoire relative to the other AIBDs. Further validation of the identified autoantibodies will shed light on their potentially pathogenic role.